2019
DOI: 10.1177/2325967118818413
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Resonance Imaging Findings of the Asymptomatic Elbow Predict Injuries and Surgery in Major League Baseball Pitchers

Abstract: Background:Repetitive pitching produces significant stress on the elbow that may result in structural abnormalities discernable on magnetic resonance imaging (MRI) without causing symptoms.Purpose:To determine whether there exists an association between subclinical MRI findings in asymptomatic elbows of Major League Baseball (MLB) players and future placement on the disabled list (DL) or future operative procedure.Study Design:Cohort study; Level of evidence, 3.Methods:MRI scans of the elbows of professional-l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 29 publications
0
25
1
Order By: Relevance
“…However, it is clear that the MRI findings identified here progressed over the course of 3 years. Based on prior studies showing subclinical UCL changes on MRI in up to 53% to 65% of high school pitchers 5,22 and 34% to 87% of professional pitchers, 4,7 these structural changes will likely continue to progress in athletes involved in ongoing competition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is clear that the MRI findings identified here progressed over the course of 3 years. Based on prior studies showing subclinical UCL changes on MRI in up to 53% to 65% of high school pitchers 5,22 and 34% to 87% of professional pitchers, 4,7 these structural changes will likely continue to progress in athletes involved in ongoing competition.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, there is evidence to suggest that asymptomatic imaging findings in the throwing elbows of professional baseball players may be precursors to subsequent serious injury. 4 Garcia et al 4 found that in 41 asymptomatic MLB pitchers with no known prior elbow injuries, certain MRI findings, specifically UCL heterogeneity, humeral-sided partial tears, and posteromedial impingement, correlated with future inferior pitching performance, placement on the disabled list, and need for elbow surgery. The primarily medial elbow abnormalities in the current study may represent an early stage in this progression.…”
Section: Discussionmentioning
confidence: 99%
“…Garcia et al 8 retrospectively investigated 41 Major League Baseball pitchers who had no prior injured list placement; 39% of these patients had normal findings on MRI of the elbow and 61% had abnormal findings, at a baseline assessment. The authors defined “injured” as being placed on the injured list, while the reverse case was defined as “healthy.” The authors demonstrated that MRI findings of posteromedial impingement, UCL heterogeneity, and humeral-side partial UCL tears were significantly correlated with future placement in the injured list for elbow abnormalities.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that elbow abnormalities seen on magnetic resonance imaging (MRI) were relatively common in 53.1% of young asymptomatic baseball players aged 9–13 years 6 , 65.0% of asymptomatic high school baseball players aged 15–19 years 7 , and 61.0% of asymptomatic professional baseball players 8 . These studies 6 8 suggest that the detection of anatomical failures in the elbow based on symptoms alone is inaccurate because although a player may be asymptomatic, there could be underlying abnormalities. Thus, the second phase of prevention involves the coexistence of elbow joint anatomical failures and an asymptomatic condition that allows unhindered throwing.…”
Section: Introductionmentioning
confidence: 99%
“…MRI is the reference standard for UCL injury diagnosis. MLB protocols often include MRI screening in pitchers to help predict future performance and UCL injury risk, although such predictions from standard MRI yield variable results [15,16]. This difficulty in part relates to suboptimal rendering of the UCL on the imaging planes obtained from conventional patient positioning for elbow MRI.…”
Section: Accepted Manuscriptmentioning
confidence: 99%